PENGEMBANGAN MULTIMEDIA PEMBELAJARAN SD PADA MATERI BENDA HIDUP DAN BENDA TAK HIDUP DI LINGKUNGAN SEKITAR TEMA 7 SUBTEMA 1 KELAS SATU (1) - Arsita Mutiara; Ayu Popy Yana; Ambyah Harjanto (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2019)
The purpose of this research is to develop multimedia products as an alternative media in learning in elementary schools. This research is a research and development or Research and Development (R&D). Borg and Gall. The results of this study are class 1 learning videos Theme 7 Sub-theme 1 material on living materials and non-living objects in the surrounding environment. The conclusion of this study is that it is important for teachers to have technological literacy to develop multimedia as a learning support so that students are able to understand the material properly and correctly so as to improve the results of students' cognitive and applications in everyday life. The suggestion from this research is that the resulting product must go through validation and trial before it is used or applied to students.